The Effect of a Care Bundle on the Rate of Blood Culture Contamination in a General Intensive Care Unit - Fani Veini; Michael Samarkos; Pantazis-Michael Voutsinas; Anastasia Kotanidou (Antibiotics)
Background/objectives: Blood culture (BC) contamination is a frequent problem which leads to increased laboratory workload, inappropriate use of antibiotics and the associated adverse events, and increased healthcare costs. This study prospectively examined the effect of a care bundle on BC contamination rates in a high workload ICU. Results: During the study, in total, 4236 BC vials were collected. After the intervention, the BC contamination rate decreased significantly from 6.2% to 1.3%. The incidence rate of contaminated BC sets was significantly lower following the intervention: 0.461 vs. 0.154 BC sets per 100 ICU bed-days. Overall compliance with the BC care bundle increased dramatically from 3.4% to 96.9%. Methods: We performed a before–after study in a general ICU from January 2018 to May 2019, with the intervention starting on November 2018. Blood culture sets were classified as positive, contaminated, indeterminate, and negative. We used bivariate and interrupted time series analysis to assess the effect of the intervention on BC contamination rates and other BC quality indicators. Conclusions: The BC care bundle was effective in reducing BC contamination rates and improving several quality indicators in our setting. The indeterminate BC rate is an important but understudied problem, and we suggest that it should be included in BC quality indicators as well. A significant limitation of the study was that the long-term effect of the intervention was not assessed.